THE EFFECTS OF EVODIAMINE ON SERUM TOTAL CHOLESTEROL AND TRIGLYCERIDE LEVELS ARE ASSOCIATED WITH THE ACTIVATION OF THE AMPK SIGNALING PATHWAY IN RATS WITH HYPERLIPEMIA - Yu, Hui; Hu, Hai; Gong, Wuzhuang; Yang, Li; Wang, Zhanli; Wang, Cuifeng (Archives of Biological Sciences, 2016)
Evodiamine, a naturally occurring indole alkaloid, has been reported to have numerous biological activities, including antitumor, antimicrobial and anti-inflammatory effects. Previous studies also suggest that evodiamine prevents obesity. In this study, we confirmed that evodiamine lowered the levels of serum total cholesterol (TC) and triglycerides (TG) in rats with hyperlipemia. Furthermore, our findings suggest that the activation of the AMP-activated protein kinase (AMPK) pathway might contribute in part to the effect of evodiamine on the serum levels of TC and TG. Key words: evodiamine; AMP-activated protein kinase; total cholesterol; triglycerides Received: September 4, 2015; Revised: October 14, 2015; Accepted: October 26, 2015; Published online: May 9, 2016